(untitled) (Research, Society and Development, 2022)
The biosecurity aims to prevent, minimize or eliminate the risks inherent to dental clinical activities. With the emergence of infectious-contagious diseases, especially in the post-COVID19 pandemic period, compliance with biosecurity protocols has taken on important dimensions. The present study evaluated the use of Personal Protective Equipment (PPE) in Basic Health Units in the city of Patos, Paraíba. The sample comprised 32 dentists and 29 oral health technicians. For data collection, a structured and self-administered questionnaire was used. Based on the work system adopted by the professionals, 89.6% perform four-handed work, in contrast to 13.1% who reported using two-handed work. 80.3% said they performed hand hygiene before and after the procedures. Regarding the prevalence of use of each of the PPE, the service time was 100% for gloves, 50.8% for disposable masks, 55.7% for aprons, 80.3% for hats and 26.2% for protective goggles. The main reasons given for not using the disposable mask was because they did not think it was necessary, as for the hats only 18% said they did not think it was necessary. With regard to the apron, 13.1% claimed that it was not provided by the public service, 8.2% thought it took a long time and 8.2% did not think it was necessary. 72.1% claimed that protective goggles are uncomfortable and/or work difficult. There is an evident need to apply guidance measures, so that there is a reinforcement in the biosafety of dentists, and their compliance in the routine of clinical practice.